Conducting Monetary and Credit Policy in Countries of the Former Soviet Union : Some Issues and Options - Bredenkamp, Hugh (IMF Working Papers; Working Paper ;, 1993)
This paper surveys some of the principal monetary policy issues facing countries of the former U.S.S.R. The emphasis is on the immediate problem of imposing financial discipline in these economies, to bring down inflation quickly and decisively. Possible options for the essential nominal anchor are considered, together with the problems of selecting appropriate targets and instruments for monetary policy needed to make that anchor effective. It is argued that, if the stabilization effort is to be sustained, discipline must be imposed at the micro- as well as the macro-level, and the paper suggests a second-best approach to the allocation of credit in the absence of well-functioning credit markets.